Snow on the Atlantic how cocaine came to Europe - Carretero, Nacho 1981- (Zed Books, 2018)
"Smuggling has been a way of life in Galicia for millennia. The Romans considered its windswept coast the edge of the world. To the Greeks it was from where Charon ferried souls to the Underworld. Since the Middle Ages, its shoreline has scuppered thousands of pirate ships. But the history of Cape Finisterre is no fiction and by the late twentieth century a new and exotic cargo flooded the cape's ports and fishing villages"--Page 4 of cover
Keywords: Drug traffic / Spain / Galicia (Region); Cocaine industry / Spain / Galicia (Region); Drug control / Spain / Galicia (Region)